Delaying ripening using 1-MCP reveals chilling injury symptom development at the putative chilling threshold temperature for mature green banana - Chang, Lan-Yen; Sargent, Steven A.; Kim, Jeongim; Brecht, Jeffrey K. (Frontiers in Plant Science, 2022)
Storage at the putative chilling threshold temperature (CTT) to avoid chilling injury still limits postharvest handling of tropical fruit like banana in that ripening may occur at the CTT. To determine whether chilling injury (CI) symptoms would develop in mature green (MG) banana fruit if the CTT exposure was extended by inhibiting ethylene action and thus ripening, 1-methylcyclopropene (1-MCP) was applied. Individual ‘fingers’ from multiple ‘clusters’ of MG bananas were either immersed in water or 50 µg L-1 1-MCP (a.i.) solution and each treatment was divided into three subgroups for storage at 5.0 °C (severe CI), 13.0 °C (mild CI), or 14.0 °C (CTT) +/- 0.1 °C. 1-MCP delayed ripening in terms of color change for 10 d for fruit stored at the CTT. As hypothesized, longer exposure of MG banana fruit to the CTT of 14.0 °C without onset of ripening as was allowed by prior 1-MCP treatment allowed CI to develop at that normally non-chilling temperature. Vascular browning was the first visual and most sensitive CI symptom in the experiment and was observed on Day 4 at 5.0 °C, Day 10 at 13.0 °C, Day 19 at 14.0 °C without 1-MCP, and on Day 28 at 14.0 °C with 1-MCP. Using a 1-MCP pre-treatment to remove the influence of ethylene from bananas stored at 13C or 14C also resulted in slight reduction in vascular browning severity. In conclusion, a putative safe temperature may become a CI temperature if the shelf-life-limiting factor is removed, allowing longer exposure. Chilling at the CTT caused relatively mild injury on fruit, and vascular browning is a sensitive indicator of CI status, while the light-adapted quantum yield of photosystem II [Y(II)] could be a non-destructive indicator of early CI stress in MG banana. Fruit at 13.0/14.0 °C developed CI symptoms slightly later with 1-MCP than without 1-MCP. This suggests that ethylene might be involved in early CI symptom development.